Degrees of Epistemic Dependence: An Extension of Pritchard’s Response to Epistemic Situationism - Clemente, Noel L (Archīum Ateneo, 2021)
Pritchard defends virtue epistemology from epistemic situationism by appealing to the notion of epistemic dependence: if knowledge acquisition is sometimes allowed to depend on factors outside the cognitive agency of the subject, then this modest form of virtue epistemology escapes the threat of the situationist challenge. This lowering of the threshold of cognitive agency required for knowledge raises the question of how to demarcate between acquisitions of true belief influenced by situational factors that count as knowledge, and those that do not. I fill this gap by proposing that the dependence of knowledge acquisition on external factors comes in degrees, which allows us to look for a right degree of epistemic dependence (a sort of Aristotelian mean) such that it both agrees with the situationist research and preserves the normative appeal of virtue epistemology.